PENINGKATAN PROSES DAN HASIL BELAJAR IPA MENGGUNAKAN MODEL PEMBELAJARAN MIND MAPPING - Apdoludin Apdoludin; Nurhayati Nurhayati (Jurnal Muara Pendidikan, 2023)
This research was motivated by the low learning process and results in science learning in class VI at SDN 296/VI Rantau Panjang. The aim of this research is to improve the science learning process and outcomes using the Mind Mapping model in class VI at SDN 296/VI Rantau Panjang. This research is a classroom action research consisting of two cycles. Each cycle consists of two meetings. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The subjects of this research were Class VI students at SDN 296/VI Rantau Panjang. This research was carried out in the second semester of the 2021/2022 academic year. At SDN 296/VI Rantau Panjang. This research data was collected using qualitative and quantitative data analysis techniques. The results of research data analysis show that the use of the Mind Mapping model can improve the process and outcomes of class VI science learning at SDN 296/VI Rantau Panjang. Details of the results of educators' observations in cycle I with an average of 79.16% and in cycle II it was 88.09% with the Good category. The results of student observations in cycle I were 68.75% and in cycle II were 75%. Meanwhile, classical completeness in cycle I obtained an average value of student learning outcomes of 43.75%, increasing to 81.25% in cycle II. It was concluded that the use of the Mind Mapping model can improve the science learning process and outcomes